The Relationship Of Frequency Of Instant Food Consumption And Energy Drinks’ Consumption With Prevalence Of Caries - Tiarma Talenta Theresia; Goalbertus Goenawan; Fadila Hanoum Nurifai (Jurnal Kesehatan Gigi, 2023)
Background: Basic Health Research (RISKESDAS) 2018 shows West Java province has the highest dental caries problem (45.66%) even higher than the national average (45.3%). The increase in the percentage of people who have problems with caries in the community caused by bad habits of consuming instant food and energy drinks that can trigger acidic conditions in the mouth. Objective: To determine the relationship between the frequency of consumption of instant food and energy drinks with the prevalence of caries at the age of 15–24 years in West Java in 2018. Methods: This type of research is an analytical observational with design cross-sectional. This study uses secondary data from RISKESDAS 2018. Results: From chi-square test, p-value of 0.568 means that there is no significant relationship between the frequency of consumption of energy drinks and the prevalence of caries, the DMF-T value, while the relationship between the frequency of consumption of instant food and the prevalence of caries is DMF-T with p-value of 0.349 also has no significant relationship. Conclusion: Frequency of consumption of instant food and energy drinks is not the only factor that determines the occurrence of caries.